(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
This work considers the solution of third-order linear homogeneous fuzzy ordinary dif ferential equations (FODEs) based on the fuzzy Laplace transform method under the generalized Hukuhara differentiability concept. The results of the third-order linear homo geneous is established and tested on some existing biomathematical models. C++ code is used to test the accuracy of the method. Finally, a recommendation for further studies is made on the establishment of results for odd- and even-order FODEs.